DEVELOPMENT ANALYSIS OF CREATIVE THINKING TEST INSTRUMENTS ON NATURAL SCIENCE MATERIALS - Yul Ifda Tanjung; Titis Wulandari; Festiyed Festiyed; Yerimadesi Yerimadesi; Yuni Ahda (Jurnal Pendidikan Fisika, 2023)
Creativity is an important part of improving learning achievement and readiness to face the globalization era which requires innovation. The success of learning creativity can be assessed through an appropriate holistic assessment instrument that contains indicators of creative thinking. Based on that, the purpose of this study is to describe the development of creativity assessment instruments that have been carried out by previous researchers through journal literature sources. The research method uses a systematic literature review of 13 selected articles that meet the criteria for achieving the research objectives. From the analysis of the literature review, conclusions are drawn, 1) Creative thinking instruments have been developed through the 4D research model, ADDIE and Borg & Gall with their respective stages, 2) Aspects of creative thinking used in developing tests refer to Torrance's theory (fluency, flexibility, originality, and elaboration). 3) In the technique of making a creative thinking item that refers to Torrance's theory, these four indicators must simultaneously form the basis for making questions. This means that through one creative thinking question can measuring fluency, flexibility, originality, and detail of the answers given by the test takers, 4) Testing the feasibility of creative thinking instruments includes validity, reliability, practicality, effectiveness, and item analysis (distinguishing power and level of difficulty).